Gnistan: the spark: a support center for people affected by cancer - Ståhl, Agnes (My University, 2021)
At some point in life most people will be affected by cancer, it is a widespread disease, affecting both the patient and everyone close to them. Getting diagnosed with cancer is tough, medical treatment is important but so is mental support. Today there seems to be a gap between the healthcare system and the mental support both during and after treatment. About 60.000 persons in Sweden get a cancer diagnose each year. A support center aims to create a place where people affected by cancer can relax, recharge and become stronger. It is also about finding a way to remove the stigma and create a safe zone where it is okay to feel weak and to cry. A cancer support center is not a new concept, but it is non-existent in Gothenburg and would function as a complement to today’s healthcare. Research shows that architecture affects people’s well-being, and that nature has a healing effect. Both architecture and nature can thus help the healing process and work as positive distraction. Biophilic design is focused on our basic need to connect with nature, using it as a tool and as inspiration it helps nature being a big part of the architecture of cancer care. This thesis has been investigating how architecture and nature in a support center affects cancer patients and their loved ones. Hopefully this will contribute to the discussion about cancer treatment in Sweden and make rehabilitation and mental support a natural part of the care. By combining existing knowledge in the healthcare field with experiences told from people affected by cancer and case studies of similar places the design proposal resulted in a center close to Sahlgrenska. This new support center provides both small intimate rooms for discussion and reflection, as well as larger rooms for rehabilitation and learning. The center has a close connection with nature, from the garden on the outside to the materials on the inside. This is a place to process the cancer, learn how to live with it, how to move on from it, or how to move on without someone. The architecture in the center support these different needs that comes along over time and takes place at the same time for different people.
Keywords: Architecture, cancer, nature, biophilic design, support, recovery